Public Administration Students' Perceptions of Corpus-Driven Instructional Design in EFL - Misnawati Misnawati; Saidna Zulfiqar Bin Tahir; Yusriadi Yusriadi; Abdul Rahman; Nur Ainun Musa (Universitas Sulawesi Barat, 2026)
This study investigates the implementation of a corpus-driven instructional design in an English for Specific Purposes (ESP) course for Public Administration students. The model, grounded in constructivist learning principles and corpus-based data-driven learning, aims to enhance vocabulary acquisition by engaging students with authentic language data and corpus analysis tools, such as keyword-in-context (KWIC) analysis and collocation exercises. The study employed a qualitative research design, collecting data through semi-structured interviews with 36 second-year students. The findings revealed that students initially faced challenges adapting to corpus tools and data-driven learning but developed positive perceptions after receiving targeted instruction and support. Students reported increased confidence and motivation in their vocabulary learning after engaging with the model. Tailored learning plans, active learning activities, and continuous feedback were perceived as beneficial for vocabulary development. Overall, the instructional design was positively received by students, who appreciated its emphasis on authentic language use, learner autonomy, and personalized instruction. This study contributes to the growing body of research on corpus-based pedagogy in ESP. It offers practical guidance for language educators seeking to enhance vocabulary instruction in specialized fields through the integration of corpus analysis and data-driven learning.